The Role Of BSI KCP Banyuwangi In The Economic Recovery Of UMKM After The Covid-19 Pandemic - Aula Izatul Aini; Binti Roudhotul Fitri (ICO EDUSHA, 2023)
The occurrence of the Covid pandemic caused a decline in sales results for UMKM in Banyuwangi, many of whom experienced losses due to the Large-Scale Social Restrictions (PSBB) policy. Economic recovery requires the help of many parties, one of the things that banks also need to do. The aim of this research is to: 1) determine the role of sharia banking in efforts to improve the UMKM economy in Banyuwangi. 2) know BSI's strategy in providing UMKM financing. This type of research uses qualitative. This research has 2 informants, namely 3 key/main informants and 2 supporting informants. The data analysis technique uses Miles and Huberman theory. The results of this research show: 1) the role of sharia banking in maintaining the UMKM economy after the Covid-19 pandemic by using a restructuring program where customers are given installment concessions or tenor extensions. 2) The strategy of sharia banks in providing financing has its own concept, namely being selective, customers must be more tenacious in ideas and innovation and holding a KUR program to help and encourage business. Keyword: The role of Bank, Recovery of UMKM, and After The covid 19 Pandemic Referensi Agama, D. (2002). Alqur’an dan Terjemah. Jakarta: Bumi Aksara. Aini, A. I. (2017). Studi Komperatif Kinerja Keuangan pada Perbankan di Indonesia (Bank Rakyat Indonesia (BRI) dan BRI Syariah). Jurnal Istiqro’, 5(2), 18–36. Aini, A. I., & Niha, A. (2021). Impulse Buying Behavior Santri Perspektif Maslahah Imam Al-Ghazali. Jurnal Darussalam: Jurnal Pendidikan, Komunikasi Dan Pemikiran Hukum Islam, 12(1), 17–33. Andrianto, A., & Firmansyah, M. A. (2019). Manajemen Bank Syariah: Implementansi Teori dan Praktek. Qiara Media Pustaka. Antonio, M. S. (2001). Bank Syariah: dari teori ke praktik. Gema Insani. ARTANINGTYAS, S. E., MSi, W., Widyaningsih, I., & Sulistyarso, H. B. (2021). SEPUTAR UMKM: Peran, Permasalahan dan Pengembangannya. LPPM UPN VETERAN YOGYAKARTA. Hafizd, J. Z. (2020). Peran Bank Syariah Mandiri (BSM) Bagi Perekonomian Indonesia Di Masa Pandemi COVID-19. Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 5(2), 138–148. Kasmir, S. E. (2018). Pemasaran Bang. Prenada Media. Muheramtohadi, S. (2017). peran lembaga keuangan syariah dalam pemberdayaan UMKM di Indonesia. Muqtasid: Jurnal Ekonomi Dan Perbankan Syariah, 8(1), 65–77. Pratiwi, S. (2021). Pengaruh Penggunaan Media Sosial Dan Inovasi Produk Terhadap Perkembangan Usaha Mikro, Kecil Dan Menengah (Umkm) Di Kabupaten Lombok Timur. Universitas Muhammadiyah Malang. Suryana. (2013). Ekonomi kreatif, ekonomi baru: mengubah ide dan menciptakan peluang. Penerbit Salemba Empat. Syafii, A. M. (2001). Islmic Banking Bank Syariah dari Teori ke Praktik. Gema Insani, Jakarta. Tambunan, T. (2012). Usaha mikro kecil dan menengah di Indonesia: isu-isu penting. LP3ES. Thaha, A. F. (2020). Dampak covid-19 terhadap UMKM di Indonesia. BRAND Jurnal Ilmiah Manajemen Pemasaran, 2(1), 147–153. Yin, R. K. (2008). Studi kasus: Desain & metode.